2013
DOI: 10.1186/1472-6963-13-192
|View full text |Cite
|
Sign up to set email alerts
|

Patient and carer experience of obtaining regular prescribed medication for chronic disease in the English National Health Service: a qualitative study

Abstract: BackgroundThe increasing burden of chronic disease is recognised globally. Within the English National Health Service, patients with chronic disease comprise of half of all consultations in primary care, and 70% of inpatient bed days. The cost of prescribing long-term medications for those with physical chronic diseases is rising and there is a drive to reduce medicine wastage and costs. While current policies in England are focused on the latter, there has been little previous research on patient experience o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…57 The literature shows that patients who have their prescriptions linked directly to a pharmacy experienced greater convenience in obtaining repeat prescriptions compared to those who submit an initial request before collecting their medications per prescription. 58 One of the most cited benefits of e-prescribing systems for patients in the UK is the Prescription Prepayment Certificate (PPC) electronic service. 11 This e-service provides patients with a certificate that enables them to acquire medication at a reduced cost by letting them pay the medication cost annually or quarterly.…”
Section: E-prescribing Assimilation Stagesmentioning
confidence: 99%
“…57 The literature shows that patients who have their prescriptions linked directly to a pharmacy experienced greater convenience in obtaining repeat prescriptions compared to those who submit an initial request before collecting their medications per prescription. 58 One of the most cited benefits of e-prescribing systems for patients in the UK is the Prescription Prepayment Certificate (PPC) electronic service. 11 This e-service provides patients with a certificate that enables them to acquire medication at a reduced cost by letting them pay the medication cost annually or quarterly.…”
Section: E-prescribing Assimilation Stagesmentioning
confidence: 99%
“…This includes sensitivity to the language used by patients and carers to describe what they regard as good quality care that meets their needs and priorities, which is not always the same as that used by services or in policy. An article on patients' and carers' experiences of obtaining repeat prescriptions provides an example of this approach (Wilson, Kataria and McNeilly 2013).…”
Section: Facilitate Reviews Of Researchmentioning
confidence: 99%
“…The most common reasons cited for being dissatisfied were the inconvenience of having to pick up the prescription/ tablets more frequently, as it interferes with the working day. 23 A qualitative study 61 that investigated patients with chronic conditions' experiences of repeat prescriptions in the NHS found that patients often described shorter prescriptions as a hassle. 61 Respondents reported that managing a repeat prescription was a time-consuming task.…”
Section: Limitations Of the Evidencementioning
confidence: 99%
“…23 A qualitative study 61 that investigated patients with chronic conditions' experiences of repeat prescriptions in the NHS found that patients often described shorter prescriptions as a hassle. 61 Respondents reported that managing a repeat prescription was a time-consuming task. In a response to a call for evidence for the DH's review of prescription charges for those with chronic conditions, Katherine White (chair of the Addison's Disease Self-Help Group) describes the 28-day prescription policy as disempowering, claiming that it causes anxiety for patients when they are running low on a prescription, and constrains their ability to travel.…”
Section: Limitations Of the Evidencementioning
confidence: 99%